Ten years after the Dutch public health campaign on folic acid: the continuing challenge - de Walle, Hermien E. K. (Springer-Verlag, 2008)
BACKGROUND: Folic acid use in the periconceptional period reduces the risk of neural tube defects (NTDs). However, applying this knowledge in daily practice is not an easy task. We report here the current level of folic acid use in the Netherlands and discuss the figures within the framework of a national governmental campaign held in 1995 promoting the use of folic acid and the professional interventions undertaken since then. METHODS: We carried out six studies in the northern Netherlands during 1995, 1996, 1998, 2000, 2003 and 2005, respectively. The same methodology in the same health professionals’ practices was followed in all studies. Pregnant women attending their first or second antenatal visit were asked to fill in a questionnaire aimed at assessing their awareness and use of folic acid. RESULTS: In 2005, most of the pregnant women used folic acid “at some time in their pregnancy”, and 51% used it for the entire advised period. Prior knowledge on the protective affect of folic acid and on the period of use was strongly related to the level of education. The use of folic acid in a previous pregnancy [odds ratio (OR) 3.9, 95% confidence interval (95% CI) 1.6–9.9], the use of an oral contraceptive (OR 2.1, 95% CI 1.1–4.1) and parity (OR 0.08, 95% CI 0.01–0.5) significantly predicted the current correct use. The most recent figures revealed that there is still a large gap between more highly and less educated women in terms of taking folic acid in the advised period: 63 versus 31%, respectively. DISCUSSION: The aim of the Dutch Ministry of Health is to have 70% of Dutch women wanting to become pregnant use folic acid supplements in the advised period by 2010. While this level has almost been reached among more highly educated women (63%), it will take a great deal more effort, money and creativity to achieve the necessary increase from the current level of 31% among women with a lower educational background.